Highly Photostable and Luminescent Donor–Acceptor Molecules for Ultrasensitive Detection of Sulfur Mustard. Issue 4 (4th January 2021) - Cui, Linfeng; Gong, Yanjun; Cheng, Chuanqin; Guo, Yongxian; Xiong, Wei; Ji, Hongwei; Jiang, Lang; Zhao, Jincai; Che, Yanke
Abstract: Real‐time, high signal intensity, and prolonged detection is challenging because of the rarity of fluorophores with both high photostability and luminescence efficiency. In this work, new donor–acceptor (D–A) molecules for overcoming these limitations are reported. A hybridized local and an intramolecular charge‐transfer excited state is demonstrated to afford high photoluminescence efficiency of these D–A molecules in solution (≈100%). The twisted molecular structure and bulky alkyl chains effectively suppress π – π and dipole–dipole interactions, enabling high luminescence efficiency of 1 and 2 in the solid state (≈94% and 100%). Furthermore, two D–A aggregates exhibit high photostability as evidenced by 4% and 8% of the fluorescence decreasing after 6 h of continuous irradiation in air, which is in sharp contrast to ≈95% of fluorescence decreasing in a reference compound. Importantly, with these molecules, ultrasensitive detection of sulfur mustard (SM) with a record limit of 10 ppb and selective detection of SM in complex matrices are achieved. Abstract : Two new donor–acceptor molecules that exhibit high photostability and photoluminescence efficiency (close to unity) both in solution and in the solid state are developed. Their application in fluorescence sensor is well illustrated by utilizing 1 porous films to ultrasensitively and selectively detect 10 ppb sulfur mustard vapor.